(3eYQV GdeOf (B6: (3GddO GdMOjbI GdeZqjHI s (Birzeit University Museum, 2018)
Lydda is a demographically divided city that has gone through a systematic engineered process of displacement of its native Palestinian inhabitants especially the 1948 Nakb. The city was planned to be a modern utopian garden city during the British Mandate by Clifford Holliday and Otto Polcheck and was intended to host only British colonisers; it was however looked upon with an Orientalist gaze for preserving its underdeveloped biblical landscape in areas where the local population lived. It offered a strategic train junction that connected North Africa with Lebanon and Syria, and through its airport, military and civilian flights connected the city with the rest of the world. Cities Exhibition 6 examines the controversies and analogies dealing with the imported British colonial planning paradigm and what that entails from post-industrial spatial forms and ethos, the transformation of Lydda to an ethnically cleansed and segregated city that had been despotically altered and the systematic racial planning policies that aimed at disempowering and suppressing PAlestinian communities in favour of Jewish immigrants.
Arabic; English
Keywords: NA1-60 Architecture- General